Explosive Properties of a High Explosive Composition Based on cis-1,3,4,6-Tetranitrooctahydroimidazo-[4,5-d]imidazole and 1,1-Diamino-2,2-dinitroethene - Hussein, Ahmed Khaled Mohamed; Elbeih, Ahmed Ikhlas Mohamed; Jungová, Marcela; Zeman, Svatopluk (My University, 2018)
In this work, preparation and characterization of a plastic bonded explosive (PBX) based on a mixture of cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) and 1,1-diamino-2,2-dinitroethene (DADNE orFOX-7) bonded by poly-dimethyl siloxane binder (PDMS) were investigated. Impact and friction sensitivities were determined. Detonation velocity was measured and the detonation characteristics were determined by the EXPLO 5 thermodynamic code. Relative explosive strength was determined using the ballistic mortar test. For comparison, four individual cyclic nitramines, RDX (1,3,5-trinitro-1,3,5-triazinane), beta-HMX (beta-1,3,5,7-tetranitro-1,3,5,7-tetrazocane), BCHMX and epsilon-CL20 (epsilon-2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane, epsilon-HNIW) in addition to their PBXs bonded by the same polymeric matrix were studied. Also traditional plastic explosives such as Czech plastic explosive (SEMTEX 10) and Egyptian Plastic Explosive (EPX-1) were included in the study. The results confirmed that BCHMX/FOX7-Sil has the lowest impact and friction sensitivity of all the studied samples and its detonation velocity and pressure are higher than the traditional PETN plastic explosives
Výbušinářské vlastnosti brizantní kompozice na bázi cis-1, 3, 4, 6-etranitrooctahydroimidazo-[4,5-d] imidazol a 1,1-di-amino-2, 2-dinitroethenu (BCHMX/FOX-7)
Keywords: BCHMX; FOX-7; nitramines; sensitivity; detonation characteristics; BCHMX; FOX-7; nitraminy; citlivost; detonační charakteristiky